DIAGNOSTIC IMAGING OF CARDIAC MYXOMAS: A DESCRIPTIVE ANALYSIS OF IMAGING FINDINGS BASED ON PUBLISHED CASE REPORTS - Martins, Leandro Alves (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2025)
Cardiac myxoma is the most frequent primary cardiac tumor, although it is rare in the general population. Despite being benign, it can cause serious complications such as obstructions, embolic events, and sudden death. The accuracy of imaging methods is essential for diagnosis and therapeutic planning. The objective was to describe the main imaging findings used in the diagnosis of cardiac myxomas based on published case reports. This narrative review of case reports adopted a structured approach for study selection and data presentation, with previously defined inclusion and exclusion criteria, acknowledging the inherent limitations of case-based evidence. The PubMed database was searched using MeSH terms related to cardiac myxoma and imaging modalities, covering the period from 2020 to January 2025, restricted to articles with free full text. Case reports describing the use of imaging techniques in the diagnosis of cardiac myxoma were included. Data regarding imaging modality, tumor location, radiological findings, and patient characteristics were extracted and descriptively summarized. Thirty-six studies, comprising 46 case reports, were included. Transthoracic echocardiography was the most frequently used initial imaging modality, often complemented by transesophageal echocardiography, magnetic resonance imaging, and computed tomography. A predominance of myxomas located in the left atrium was observed. Cardiac magnetic resonance imaging demonstrated consistent imaging patterns that aided in differentiating myxoma from thrombus in most reported cases, particularly through the analysis of signal characteristics on T1- and T2-weighted images and gadolinium enhancement patterns. Computed tomography proved effective in detecting calcifications, supporting surgical planning, and providing detailed anatomical assessment.